Association between family dinner frequency and mental health in children and adolescents; the CASPIAN-V study. (3rd July 2020) - Karimi, Golgis; Vard, Bahareh; Riyahi, Roya; Motlagh, Mohammad Esmail; Heshmat, Ramin; Kelishadi, Roya
Abstract: This cross-sectional study was conducted among 14, 400 Iranian students, aged 7–18 years to determine the association between the frequency of family dinner and mental health. Family dinner frequency, family relationship, life satisfaction (LS), self-perceived health and anxiety were assessed by validated questionnaires. Of 14, 274 participants, 50.6% were boys and 71.4% were urban residents, with a mean (SD) age of 12.28 (3.16) years. Family dinner frequency was significantly correlated with LS (boys: β = 0.27, p  < .001; girls: β = 0.26, p  < .001) and socio-economic status (boys: β = 0.05, p  < .001; girls: β = 0.02, p  < .001). A significant inverse association was observed between family dinner frequency and family relationship with anxiety, which was more evident in boys than in girls ( p  < .05). This study underscores the important role of family dinner frequency with lower anxiety in children as well as a better family relationship with better LS.